Therapeutic Response of miR-145 Micelles on Patient-Derived Vascular Smooth Muscle Cells - Patel, Neil; Chin, Deborah D.; Magee, Gregory A.; Chung, Eun Ji (Frontiers in Digital Health, 2022)
During atherosclerosis, vascular smooth muscle cells (VSMCs) undergo a phenotypic transition from a healthy contractile state into pathological phenotypes including a proliferative and migratory, synthetic phenotype and osteochondrogenic-like phenotype that exacerbate plaques. Thus, inhibiting the transition of healthy, quiescent VSMCs to atherogenic cell types has the potential to mitigate atherosclerosis. To that end, previously, we reported that delivery of microRNA-145 (miR-145, a potent gatekeeper of the contractile VSMC phenotype) using nanoparticle micelles limited atherosclerotic plaque growth in murine models of atherosclerosis. Building on this preclinical data and towards clinical application, in this study, we tested the therapeutic viability of miR-145 micelles on patient-derived VSMCs and evaluated their effects based on disease severity. We collected vascular tissues from 11 patients with healthy, moderate, or severe stages of atherosclerosis that were discarded following vascular surgery or organ transplant, and isolated VSMCs from these tissues. We found that with increasing disease severity, patient-derived VSMCs had decreasing levels of contractile markers (miR-145, ACTA2, Myh11) and increasing levels of synthetic markers (KLF4, KLF5, and ELK1). Treatment with miR-145 micelles showed that an increase in disease severity correlated with a more robust response to therapy in VSMCs. Notably, miR-145 micelle therapy rescued contractile marker expression to baseline contractile levels in VSMCs derived from the most severely diseased tissues. As such, we demonstrate the use of miR-145 micelles across different stages of atherosclerosis disease and present further evidence of the translatability of miR-145 micelle treatment for atherosclerosis.